Efficacy and safety of nasobiliary drain in patients with postoperative biliary leakage - Tunç, Nurettın; Girgin, Mustafa; Bahçecioğlu, İbrahim Halil; Yalniz, Mehmet (My University, 2019)
The aim of the present study is to examine the efficacy of nasobiliary drainage with endoscopic retrograde cholangiopancreaticography on the necessity of a subsequent surgery or endoscopic or radiological intervention for patients with biliary leakage. 37 cases of bile leakage were followed. The location of the biliary leakage with endoscopic retrograde cholangiopancreaticography, the presence of post-endoscopic retrograde cholangiopancreaticography complications and whether a second surgery was performed were retrospectively reviewed. The study sample included 37 patients, namely 22 women and 15 men. The average age of the patients was 45.6 years. The biliary leakage identified among the patients (26/37) by way of the endoscopic retrograde cholangiopancreaticography procedure was located in their intrahepatic biliary tract in 27.0%, their gallbladder cavity in 37.8%, and the hilar region in 5.4%, and was unspecified suspected leakage in 29.7%. 24 (64.8%) of the cases had undergone cholecystectomy and 10 (27.0%) hydatid cyst surgery, while one of case lobectomy + cholecystectomy and 2 of sharp-object injuries. Their average duration of hospitalisation was 17.7 days. The cases that had undergone surgery for hydatid cysts exhibited an average duration of hospitalisation of 24.6 days. Nasobiliary drainage had secured medical treatment without the need for a surgical intervention in 91.9% of the cases. Experienced medical centres should primarily prefer the effective and reliable procedure of endoscopic retrograde cholangiopancreaticography and the administration of nasobiliary drain as highly successful method for the non-surgical treatment of postoperative biliary leakage.
Keywords: Gastroenteroloji ve Hepatoloji; Cerrahi